Hypersensitivity to Suture Anchors - Masafumi Goto; Masafumi Gotoh; Yasuhiro Mitsui; Ryo Tanesue; Takahiro Okawa; Fujio Higuchi; Naoto Shiba (Case Reports in Orthopedics)
Hypersensitivity to suture anchor is extremely rare. Herein, we present a case in which hypersensitivity to suture anchor was strongly suspected. The right rotator cuff of a 50-year-old woman was repaired with a metal suture anchor. Three weeks after the surgery, she developed erythema around her face, trunk, and hands, accompanied by itching. Infection was unlikely because no abnormalities were detected by blood testing or by medical examination. Suspicious of a metallic allergy, a dermatologist performed a patch testing 6 months after the first surgery. The patient had negative reactions to tests for titanium, aluminum, and vanadium, which were the principal components of the suture anchor. The anchor was removed 7 months after the first surgery, and the erythema disappeared immediately. When allergic symptoms occur and persist after the use of a metal anchor, removal should be considered as a treatment option even if the patch test result is negative.